Computational Role of Polymer-Based Ternary Hybrid Nanofluid Between Convergent/Divergent Channels With Radiation and Stretchable/Shrinkable Wall Effects - Mohamed Kezzar; Amar Dib; Umair Khan; Ismail Tabet; Mohamed R. Sari; Syed Modassir Hussain (Journal of Mathematics)
The present article introduces a numerical and analytical study of ternary hybrid nanoparticle (Cu, Fe3O4, and SiO2) with base fluid of Polymer. Heat Transfer on MHD Jeffery–Hamel flow with multiple effects is taken into account. Innovative results in the current study are obtained by utilizing the combined effect of nonlinear thermal radiation and the stretchable/shrinkable walls. The modelled partial differential equations underwent a transformation to nonlinear ordinary differential equations using similarity transformation. Subsequently, an analytical solution was obtained by employing the ADM method. To validate the accuracy of the results, a comparison was made with outcomes from the HAM-based Mathematica package and the Runge–Kutta–Fehlberg fourth-fifth order approach featuring shooting technique. The effect of diverse parameters on dimensionless velocity, temperature profiles, skin friction coefficient and Nusselt number has been investigated and interpreted through the tabular and graphical results. When nanoparticles are present in the base fluid, the rate of heat transmission is upsurged for both convergent-divergent channels. In addition, the Nusselt number boosts with the augment of nanoparticle volume fraction. Results obtained also reveal that the nanofluid temperature upsurges in the stretching zone (C>0) and drops in the shrinking zone (C<0).